Leiomyosarcoma of the transverse colon with lymph node metastasis and malignant transformation: a case report - Tomoya Tago; Shuji Suzuki; Jun Kuroda; Ryutaro Udou; Kiyotaka Nishida; Yukio Oshiro; Jirou Shimazaki; Keni Kou; Yukio Morishita; Mitsugi Shimoda (Surgical Case Reports, 2020)
Abstract Background The concept of GIST was established in 1998, clearly differentiating between gastrointestinal leiomyosarcoma and GISTs among gastrointestinal mesenchymal tumors. Lymph node metastasis is extremely rare in true gastrointestinal leiomyosarcoma, and there are no reports of malignant transformation from leiomyoma. Case presentation The patient was an old woman who had undergone endoscopic mucosal resection for an Is polyp on the left side of the transverse colon at the age of 73. She was diagnosed with leiomyoma with positive surgical margins. Subsequently, she presented to our institution with a sensation of pressure in the upper abdominal region as a chief complaint at the age of 76 years. Abdominal computed tomography and colorectal endoscopy showed a tumor lesion with invagination of the intestines in the transverse colon, the same site as that of the previously resected leiomyoma. A biopsy suggested a smooth muscle tumor, and we performed partial left transverse colectomy and lymph node dissection under a diagnosis of recurrence and enlargement of the previously incompletely resected leiomyoma. Histopathological examination revealed spindle-shaped tumor cells, and the mitotic activity was 30–40/10 high-power field. Tumor cells were immunohistologically positive for α-smooth muscle actin and h-caldesmon; partially positive for desmin; negative for c-kit, CD34, DOG-1, and the S-100 protein; and showed a Ki-67 labeling index of 70–80%. She was diagnosed with leiomyosarcoma malignantly transformed from leiomyoma. Metastasis was found in 1 of the 14 resected lymph nodes. The patient did not undergo adjuvant chemotherapy, but has survived with no recurrence at 2 years after the surgery. Conclusions We have reported a case of leiomyosarcoma of the transverse colon with lymph node metastasis that was malignantly transformed from a leiomyoma.